Sustainable agriculture: An assessment of Brazil's family farm programmes in scaling up agroecological food production - Ben McKay; Ryan Nehring (International Policy Centre for Inclusive Growth (IPC-IG), 2014)
Agroecology in Brazil is quickly gaining momentum with the recent passing of Decree 7.794 of 20 August 2012 for a National Policy for Agroecology and Organic Production (PLANAPO) and strong support from civil society organisations. While PLANAPO was officially launched on 17 October 2013, the implementation of this policy in terms of outreach, coverage and effectiveness is yet to be determined. This study examines agroecological farm production in Brazil and the effectiveness of family farm programmes and policies in supporting a transition towards agroecological production. We also reveal the importance of family farms in Brazil and examine public policies and programmes implemented to support family farmers2 in the country. We start this analysis by discussing the `Brazilian agricultural dilemma' and its inherent contradictions and conflicts. We then provide a comprehensive policy analysis based on government reports and complement this analysis with our empirical data based on field work conducted in April 2012. Based on these findings, we highlight several weaknesses and failures and implications going forward for scaling up agroecological production. With timely and relevant data, we hope this Working Paper contributes to the policy discussion based on agroecology and provides some key insights for future design and implementation.
Keywords: 330